UPAYA MENANAMKAN NILAI-NILAI RELIGIUS PADA SANTRI PPS TAHFIDZ AR-RAUDHAH TINGKAT ULA (MADRASAH IBTIDAIYAH) DI YAYASAN CAHAYA AMANAH AR-RAUDHAH KOTA BANJARBARU - Nur Amaliyah Hayati; Siti Rahmawati (Program Studi PGMI STAI Al Falah Banjarbaru, 2026)
This study discusses the Efforts to Instill Religious Values ​​in Students of PPS Tahfidz Ar-Raudhah Ula Level (Madrasah Ibtidaiyah) Banjarbaru City. This study aims to determine how efforts to instill religious values ​​in students and what are the supporting and inhibiting factors. The subjects in this study were Ula Level teachers and Foundation advisors, while the objects in this study were efforts to instill religious values ​​in students and what are the supporting and inhibiting factors. Data collection was carried out using observation techniques, structured interviews and documentation. Data processing was carried out using data collection techniques, data classification, editing and data interpretation, qualitatively, then drawing conclusions inductively by describing each data obtained to obtain the researcher's conclusions. Based on the results of the study, it is known that efforts to instill religious values ​​in students of PPS Tahfidz Ar-Raudhah Ula Level (Madrasah Ibtidaiyah) Banjarbaru City have been implemented through several ways, namely the process of instilling religious values ​​through moral knowing, moral feeling, and moral action. The religious values ​​instilled include worship, the spirit of jihad, morals and discipline, and the values ​​of trust and sincerity. These religious values ​​are instilled through role models, habituation, and counseling. Supporting factors include self-awareness, the community environment, family, and parents, while inhibiting factors include a lack of knowledge, an unconducive community environment, and the influence of social media.